Protective and stress factors for psychological distress: A comparative analysis of LGB and non-LGB older adults - Ribeiro-Gonçalves, José Alberto (2025)
Objectives: Population ageing raises major public health and psychosocial challenges. Particularly, lesbian, gay, and bisexual (LGB) older people may face increased vulnerabilities and marginalization when compared to their non-LGB (heterosexual) counterparts, which may entail more risks for their mental health. The aim of this study was to comparatively evaluate the levels of protective – social support, spirituality, and resilience and stress factors – loneliness and ageism – among LGB and nonLGB older adults, and their impact on psychological distress (PD). Method: A sample of 647 people aged 60years or older (M=66.01; SD = 4.93) was collected, 368 non-LGB and 279 LGB. Participation was carried out through an online survey in Portugal. Results: LGB older adults had lower scores on all protective factors, except on social support from friends, and higher levels on all stress factors, except on hostile ageism, compared to non-LGB older adults. Further, resilience and loneliness were the main predictors of PD regardless of the sexual orientation. Stress factors explained the levels of PD over and above the effects of protective factors, both among LGB and non-LGB older adults. Conclusion: Psychological distress in aging presents different protective and stressful factors according to the sexual orientation of older adults. More comparative studies are suggested in the intersection between ageing and sexual orientation.